An Anti-Political Revolution: Reading the Azusa Street Revival and Civil Rights Movement within the Black Radical Tradition - Justice, David (Black theology, 2025)
It is necessary to draw from and push forward the Black radical tradition to realize a world free from racial capitalism. Drawing on the work of Keri Day, I argue that the Azusa Street Revival represents a stream of the Black radical tradition. Further, I contend that the civil rights movement associated with Martin Luther King Jr. represented a continuation of this stream. Specifically, I argue that the Azusa Street Revival and the Beloved Community as envisioned and built by King formed what I call anti-political communities. I refer to these communities as anti-political because they reject the politics of racial capitalism and begin the work of building outside its domain via the Black radical tradition. These anti-political communities tore down racial capitalism through the new kind of community they built, and they have lessons for how we can do so in the present.